Vi antigen from Salmonella typhosa and immunity against typhoid fever. 11. Safety and antigenicity in humans. - Levin, D M (1975)
Safety and antigenicity of a purified preparation of Salmonella typhosa Vi antigen was evaluated in human volunteers. Dosages of Vi antigen at 25, 50, and 100 mug were less toxic than U.S. standard typhoid vaccine (lot 6A) containing 5 X 10(8) bacteria per dosage. Vi antigen in comparison with the standard typhoid vaccine induced higher hemagglutinating antibody but lower bactericidal antibody responses.